A FUZZY LOGIC CONTROLLER FOR STABILITY VOLTAGE AND MAXIMUM ENERGY EXTRACTION FOR FIXED SPEED WIND POWER GENERATION SYSTEMS - Widodo Widodo; Winarno Winarno (WAHANA, 2013)
This paper introduces two advantages of a fuzzy logic controller for the first is stability voltage and the second is maximum energy extraction for fixed speed wind power generation systems. Maximum energy extraction is determined by thetip speedratio (TSR) and the power factor of a wind turbine in order to capture the maximum efficiency and control the speed of turbine in order to control voltage stability.While the TSRand power factor were taken as output variables we propose control the tip speed of generator in surrounding the value of maximum TSR. The proposedmodel produced fuzzy logic controller can keep the voltage stability at maximum TSR and nearest. The results indicate that we can do two task (power max extraction and stability voltage) in one design.